LPA, HGF, and EGF utilize distinct combinations of signaling pathways to promote migration and invasion of MDA-MB-231 breast carcinoma cells - Harrison, Susan MW; Knifley, Teresa; Chen, Min; O’Connor, Kathleen L (BMC cancer, 2013)
Various pathways impinge on the actin-myosin pathway to facilitate cell migration and invasion including members of the Rho family of small GTPases and MAPK. However, the signaling components that are considered important for these processes vary substantially within the literature with certain pathways being favored. These distinctions in signaling pathways utilized are often attributed to differences in cell type or physiological conditions; however, these attributes have not been systematically assessed. To address this question, we analyzed the migration and invasion of MDA-MB-231 breast carcinoma cell line in response to various stimuli including lysophosphatidic acid (LPA), hepatocyte growth factor (HGF) and epidermal growth factor (EGF) and determined the involvement of select signaling pathways that impact myosin light chain phosphorylation. LPA, a potent stimulator of the Rho-ROCK pathway, surprisingly did not require the Rho-ROCK pathway to stimulate migration but instead utilized Rac and MAPK. In contrast, LPA-stimulated invasion required Rho, Rac, and MAPK. Of these three major pathways, EGF-stimulated MDA-MB-231 migration and invasion required Rho; however, Rac was essential only for invasion and MAPK was dispensable for migration. HGF signaling, interestingly, utilized the same pathways for migration and invasion, requiring Rho but not Rac signaling. Notably, the dependency of HGF-stimulated migration and invasion as well as EGF-stimulated invasion on MAPK was subject to the inhibitors used. As expected, myosin light chain kinase (MLCK), a convergence point for MAPK and Rho family GTPase signaling, was required for all six conditions. These observations suggest that, while multiple signaling pathways contribute to cancer cell motility, not all pathways operate under all conditions. Thus, our study highlights the plasticity of cancer cells to adapt to multiple migratory cues.